2016
DOI: 10.1016/j.pharmthera.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell vascular mimicry: Novel targeting opportunity in melanoma

Abstract: In 1999, the American Journal of Pathology published an article, entitled “Vascular channel formation by human melanoma cells in vivo and in vitro: vasculogenic mimicry” by Maniotis and colleagues, which ignited a spirited debate for several years and earned the journal's distinction of a “citation classic” (Maniotis et al., 1999). Tumor cell vasculogenic mimicry (VM), also known as vascular mimicry, describes the plasticity of aggressive cancer cells forming de novo vascular networks and is associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(148 citation statements)
references
References 110 publications
7
136
0
3
Order By: Relevance
“…Cancer stem cells may contribute to the formation of VM (26). VM was originally identified in malignant melanoma, and was subsequently demonstrated to be an important morphological feature of MM (27). In the present study, VM is detectable in undifferentiated MM due to stemness, which may be a useful tool for MM diagnosis.…”
Section: Discussionsupporting
confidence: 54%
“…Cancer stem cells may contribute to the formation of VM (26). VM was originally identified in malignant melanoma, and was subsequently demonstrated to be an important morphological feature of MM (27). In the present study, VM is detectable in undifferentiated MM due to stemness, which may be a useful tool for MM diagnosis.…”
Section: Discussionsupporting
confidence: 54%
“…This interplay between angiogenesis and tumor initiating cells offers the rationale for combining anti-angiogenetic agents with drugs that target CSCs (80). Novel compounds, such as CVM-1118, targeting VM and the associated stem cell and drug resistance phenotypes are under development (81).…”
Section: Discussionmentioning
confidence: 99%
“…The term VM was first coined by Mary Hendrix and described the formation of tumour-derived blood vessels and it was hypothesised that this may provide an easy access for tumour cells to the bloodstream (125). VM was first described in human melanoma where it was shown that tumour cells shown to co-express endothelial and tumour markers and formed blood vessels (125) and further studies have given insights in VM induction across a variety of cancer types including breast, ovary, lung, prostate, bladder cancer (126). VM has been associated with tumour dissemination and metastasis (127) and in SCLC it has been shown that a subpopulation of CTCs co-express VE-cadherin (a VM marker) as well as epithelial cytokeratins indicating VM is involved in CTCs dissemination (124).…”
Section: Vascular Mimicry (Vm)mentioning
confidence: 99%